1982
DOI: 10.1073/pnas.79.12.3848
|View full text |Cite
|
Sign up to set email alerts
|

Possible metabolic basis for the different immunodeficient states associated with genetic deficiencies of adenosine deaminase and purine nucleoside phosphorylase.

Abstract: An inherited deficiency of adenosine deaminase (Ado deaminase; adenosine aminohydrolase, EC 3.5.4.4) causes severe combined immunodeficiency disease in humans. A similar deficiency in purine nucleoside phosphorylase (Puo phosphorylase; purine-nucleoside:orthophosphate ribosyltransferase, EC 2.4.2.1) engenders a selective cellular immune deficit. To elucidate the possible metabolic basis for the contrasting immunologic phenotypes, we compared the toxicity toward mature resting human lymphocytes ofthe Ado deamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…2'-Deoxyguanosine, guanosine, guanine, hypoxanthine, adenine, and 2'-deoxycytidine were purchased from Sigma Chemical Co. (St. Louis, MO). 8 (11,12). These cells were originally obtained from the peripheral blood or lymph node of patients with cutaneous T cell lymphomas and have surface antigens reactive with OKT4 monoclonal antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2'-Deoxyguanosine, guanosine, guanine, hypoxanthine, adenine, and 2'-deoxycytidine were purchased from Sigma Chemical Co. (St. Louis, MO). 8 (11,12). These cells were originally obtained from the peripheral blood or lymph node of patients with cutaneous T cell lymphomas and have surface antigens reactive with OKT4 monoclonal antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Growth inhibition and GTP accumulation are prevented by hypoxanthine or adenine, but not by 2'-deoxycytidine. 8 Receivedfor publication 31 January 198.4 and in revisedform 12 July 1984. sine appears to effectively inhibit extracellular PNP activity; thus, it prolongs the extracellular half-life of 2'-deoxyguanosine and guanosine, but does not completely inhibit intracellular PNP activity in these lymphoid cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in vitro it was exquisitely toxic to normal resting peripheral blood lymphocytes and to slowly dividing malignant T cells. This ability to kill nondividing lymphocytes distinguished CdA from other commonly used chemotherapeutic agents affecting purine and pyrimidine metabolism (18,19). We also tested the anti-proliferative effects of CdA toward more than 40 bone marrow specimens from patients with acute leukemia, as compared to 20 normal bone marrow specimens (18).…”
mentioning
confidence: 99%
“…In the absence of ADA enzyme activity, dAdo is phosphorylated by cellular deoxynucleoside kinases, leading to the formation of accumulated dATP. A number of studies concluded this was likely to be the most relevant biochemical process leading to toxicity in ADA-deficient developing lymphocytes [3,4]. However, some contention was held about the relative role of the two major deoxynucleoside kinases believed to be responsible for the initial phosphorylation of dAdo, deoxycytidine kinase (dCK) and adenosine kinase (AK).…”
Section: Introductionmentioning
confidence: 99%